A systematic review of left unilateral electroconvulsive therapy. (19th April 2017) - Kellner, C. H.; Farber, K. G.; Chen, X. R.; Mehrotra, A.; Zipursky, G. D. N.
Abstract : Objective: To systematically review the published clinical trials, case series, and case reports on left unilateral (LUL) electrode placement for clinical electroconvulsive therapy (ECT). Method: PubMed, Ovid Medline, and the Cochrane Library were searched for articles concerning LUL ECT. Number of patients, efficacy, and cognitive outcomes were extracted from the papers that met our inclusion criteria. Results: A total of 52 articles were included in this review, consisting of 33 clinical trials, seven case series, and 12 case reports. Conclusion: Overall, the efficacy of LUL electrode placement for the treatment of depression and psychosis is similar to that of right unilateral (RUL) and bilateral (BL) electrode placements. Patients receiving LUL ECT tend to experience more verbal memory impairment than patients receiving RUL ECT, but less verbal impairment than patients receiving BL ECT. In contrast, patients receiving LUL ECT tended to experience the least visual and nonverbal memory impairment, compared to patients receiving RUL or BL ECT.